2006
DOI: 10.1038/nature05104
|View full text |Cite
|
Sign up to set email alerts
|

A galaxy at a redshift z = 6.96

Abstract: When galaxy formation started in the history of the Universe remains unclear. Studies of the cosmic microwave background indicate that the Universe, after initial cooling (following the Big Bang), was reheated and reionized by hot stars in newborn galaxies at a redshift in the range 6 < z < 14 (ref. 1). Though several candidate galaxies at redshift z > 7 have been identified photometrically, galaxies with spectroscopically confirmed redshifts have been confined to z < 6.6 (refs 4-8). Here we report a spectrosc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
442
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(466 citation statements)
references
References 28 publications
21
442
2
1
Order By: Relevance
“…26 -0. 24 . The lensing-corrected UV luminosity is ~1.8×10 10 L ⊙ , resulting in a star-formation rate estimate of 2.7±0.3 M ⊙ yr -1 based on the UV emission and uncorrected for dust extinction, for a Chabrier initial mass function 11 .…”
mentioning
confidence: 99%
“…26 -0. 24 . The lensing-corrected UV luminosity is ~1.8×10 10 L ⊙ , resulting in a star-formation rate estimate of 2.7±0.3 M ⊙ yr -1 based on the UV emission and uncorrected for dust extinction, for a Chabrier initial mass function 11 .…”
mentioning
confidence: 99%
“…Hu et al 2002;Kurk et al 2004;Stern et al 2005;Murayama et al 2007). In particular, Taniguchi et al (2005) report the detection of 9 spectroscopically confirmed LAE at redshifts of z ∼ 6.6 in the Subaru Deep Field (currently, the published LAE redshift record holder is at z = 6.98, Iye et al 2006). The mere presence of Lyman alpha emission in these sources provides strong evidence that they are undergoing bursts of star formation: the star formation rates of individual objects are ∼10 M yr −1 (based on their FUV luminosities) and their redshifts place them well within the end of cosmic reionization.…”
Section: Introduction: the Highest Redshift Galaxiesmentioning
confidence: 99%
“…Although Lyα emitters are among the most distant galaxies with spectroscopically confirmed redshifts (see Iye et al 2006;Ota et al 2008), few have been found at z > ∼ 7 (see e.g. Cuby et al 2007;Stark et al 2007b;Willis et al 2008;Hibon et al 2009;Sobral et al 2009).…”
Section: Introductionmentioning
confidence: 99%